Zinc, iron, manganese and cadmium released from four liming materials and their absorption by lettuce in two soils - do Amaral, Alberto Silveira; Defelipo, Braz Vitor; da Costa, Liovando Marciano; Fontes, Maurício Paulo Ferreira (Pesquisa Agropecuaria Brasileira, 1994)
A greenhouse experiment was carried out to evaluate zinc, iron, manganese and cadmium release from four liming materials applied to two distinct soil textures and their absorption by lettuce. The treatments were based on factorial experiment 2 [2 (4+1) + 1]: two soils, two lime requirements, four liming materials + CaCo3 and an additional treatment (control). They were arranged in the randomized blocks design with three replications. On the other hand, the soil pH decreased to original values after harvesting the lettuce, but the exchangeable aluminum was higher than that found in the control treatment. Absorption and accumulation of Zn, Fe, Mn and Cd in the lettuce shoots with lime materials increments was determined in both soils. The availability of Zn, Fe and Mn was higher in the sandy loam soil, but for Cd it was not observed.
Keywords: micronutrients; heavy metals